The 80/20 Rule - Murat Yılmaz (Türk Kütüphaneciliği)
The purpose of the study is to examine the meaning and the importance of the 80/20 rule for library and information science. With this purpose, in our study the theoretical and the practical studies about the 80/20 rule in the literature of library and information science are dealt with. Furthermore an example concerning the 80/20 rule is given. The database of our example is 1271 articles published on the subject of museology in the “The Bibliography of Articles in Turkish Periodicals” between 1923-2002. In our example, our database was analyzed to test the applicability of the 80/20 rule. In the result of the analysis, it was found that the 80/20 rule did not apply to our database.